Effects of government borrowing on private investments in Kenya - Caspah Lidiema (Kenya Bankers Association (KBA), 2017)
This paper analyses the effect of government domestic borrowing on private investment using an Auto Regressive Distributed Lag (ARDL) model to test for long-run and shortrun co-integration relationship between the independent variables and Gross fixed capital formation. The findings show that Domestic Debt has a negative and significant relationship with Gross fixed capital formation even though this relationship diminishes in the long run. The findings confirm that excessive domestic borrowing by the government can negatively affect investment and eventually hurt economic growth. The paper recommends the need for the government to come up with policies to govern domestic borrowing and interest rates in addition to policies that encourage financial development through boosting Small and Micro enterprises lending to encourage local investment.
Keywords: 330; Government Borrowing; Gross Domestic Savings; real interest rate; Domestic Private Investment; ARDL